A morál kulturális szociológiája és a média (Szociológiai Szemle, 2024)
During the 1990s, the moral implications of social problems have unexpectedly returned to the centre of sociological inquiry. Using Alexander’s neo-Durkheimian cultural sociology, this study explores the sociological relationships between morals and the public sphere, and morals and the media. Alexander placed the media in a conceptual space between a “real civil society” and an “ideal civil society” and with this he created the possibility of understanding the cultural role of morals in today’s society. The norm reinforcing function o f the media is important because increasing social differentiation has resulted in the exclusion of moral problems from social sub-systems and their integration into professional regulations. The conclusion of the article is that the media constitute a kind of cultural forum where the ongoing deconstruction and reconstruction of the moral order can take place with the aid of the sacrilization, desacrilization and resacrilization o f collective symbols.